Proof-of-Concept of the Virtual Reality Comprehensive Balance Assessment and Training for Sensory Organization of Dynamic Postural Control - Moon, Sanghee; Huang, Chun-Kai; Sadeghi, Maryam; Akinwuntan, Abiodun E.; Devos, Hannes (Frontiers in Bioengineering and Biotechnology, 2021)
Accurate quantification of the impact of visual, somatosensory, and vestibular systems on postural control may inform tailor-made balance intervention strategies. The aim of this proof-of-concept study was to determine the safety, sense of presence, system usability and face validity of a newly developed Virtual Reality Comprehensive Balance Assessment and Training (VR-ComBAT) in healthy young individuals. The VR-ComBAT included six balance condition: [1] stable surface with fixed virtual reality (VR) surroundings; [2] stable surface with blacked out VR surroundings; [3] stable surface with VR visual conflict; [4] unstable surface with fixed VR surroundings; [5] unstable surface with blacked out VR surroundings; and [6] unstable surface with VR visual conflict. Safety was evaluated using the number of adverse events, including scores on the Simulator Sickness Questionnaire. Sense of presence was evaluated using the igroup Presence Questionnaire (iPQ). System usability was assessed using the Systems Usability Scale (SUS). Friedman analyses with post-hoc Wilcoxon Signed Rank tests were employed to demonstrate face validity by quantifying center of pressure (COP) changes in mean distance, mean velocity, and mean frequency in the anteroposterior (AP) and mediolateral (ML) direction across the six conditions. Twenty-three participants (27.4±8.0 years old; 13 women) reported no adverse events. Participants scores on average 44.9±9.6 on the iPQ and 79.7±9.9 on the SUS. Post-hoc analyses showed that significant changes in COP-based measure when compared to baseline. The mean frequency change of COP showed direction-dependent in which the increased frequency change in AP was observed while the decreased change in ML was noted. The VR-ComBAT provides a safe, feasible, and cost-effective VR environment that demonstrates consistent sensory re-weighting between visual, somatosensory, and vestibular systems. Future studies should investigate whether VR-ComBAT can be used to inform precision rehabilitation of balance and fall prevention in older adults without and with neurological conditions.